Genetic diversity of hepatitis B virus genotypes B6, D and F among circumpolar indigenous individuals. Issue 2 (3rd July 2012) - Kowalec, K.; Minuk, G. Y.; Børresen, M. L.; Koch, A.; McMahon, B. J.; Simons, B.; Osiowy, C.
<x xml:space="preserve">Abstract</x> Summary. Hepatitis B virus (HBV) infection is highly prevalent in circumpolar indigenous peoples. However, the clinical outcome is extremely variable, such that while hepatocellular carcinoma (HCC) is uncommon in Canadian Inuit, the incidence of HCC is slightly higher in Greenlanders than in Danes, and it is especially high in Alaskan Native people infected with HBV genotypes F (HBV/F) and C (HBV/C). These differences may be associated with the genomic variability of the predominant HBV genotype in each group. The purpose of this study was to determine the rate, nature and regional susceptibility of HBV genomic mutations among circumpolar indigenous individuals. Paired serum samples, separated by 5–6 years, were analysed from Canadian and Greenlandic Inuit infected with HBV genotype B6 (HBV/B6) and HBV/D, respectively, and from Alaskan Native people infected with HBV/F, each having subsequently developed HCC. Phylogenetic and mutational analyses were performed on full‐genome sequences, and the dynamic evolution within the quasispecies population of each patient group was determined by clonal analysis of the non‐overlapping core coding region. Mutations associated with severe outcomes predominated in HBV/F, mostly within the precore/core and PreS1 region. HBV/B6 genomes exhibited higher diversity compared to HBV/D and HBV/F, particularly within the core coding region. Thus, differing mutational profiles and genetic variability were observed among different HBV genotypes predominating in circumpolar indigenous patients. The unusual observation of persistently high genetic variability with HBV/B6 despite clinical inactivity could be due to the evolution of a host‐pathogen balance, but other possible factors also need to be explored.